LIFE SKILLS: PENGRAJIN ANYAMAN ROTAN JALAN YOS SUDARSO KOTA PEKANBARU - Intan Riausa Ibrahim; Desti Irja; Daeng Ayub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of the study was to determine the level of consumer interest in life skills: rattan woven craftsmen in Yos Sudarso Street, Pekanbaru City, to find out the factors that increase the attractiveness of more attractive rattan for interest among the community, especially Pekanbaru. Formulation of the problem of how high the improvement in the work of innovation is the functional royan handicraft model as well as improving the business climate and manpower management. Besides based on the formulation of the problem and the purpose of the study, it was also obtained consumer satisfaction based on sex and age at Yos Sudarso street in Pekanbaru city. This type of research is descriptive with a quantitative approach. The population in this study were 70 rattan craftsmen in Yos Sudarso street, Pekanbaru city. This technique used is Proportionate Stratified rendom sampling. This technique is used if the population has non-homogeneous members / elements and proportionally structured instruments used in this study are questionnaires, which contain 29 statements about life skills: rattan woven craftsmen in Yos Sudarso city Pekanbaru. The data in this research greeting will be analyzed using descriptive statistics. The results of data analysis show that personal skills are classified as high mean 4.32 and SD 0.60, mean social skills 4.14 and SD 0.60, mean academic skills 4.17 and SD 0.58, and vocational skills mean 4 , 30 and SD 0.55, all of which are in a high interpretation. Furthermore, the contribution of each indicator was made into personal skills with contributions of 62.04%, contribution of social skills 70.00%, contribution of academic skills 72.60%, and contribution of vocational skills 51.50%. Rattan woven craftsmen based on demographics, which are based on sex are classified as high (mean 4.21) and based on age are classified as high (mean 4.11).Key Words: Life Skills, Craftsmen, Woven, and Rattan.